Schizophrenic Speech Potrayed in the Main Character in Canvas Movie - Fais Wahidatul Arifatin (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2023)
This research is focused on the analysis of psycholinguistics aspect. The purpose of the study is to analyze the linguistic phenomena of schizophrenia suffered by the amin character in Canvas movie which is Mary. The objectives of this research is to find out and describe the language abnormalities experienced by the main character. There are some  findings  related to schizophrenic  language  abnormalities,  from eight types that occur in this research is only five.  They  are looseness, perseveration  of  ideas,  non-logical  reasoning  (peculiar  logic),  weakening  of  goal,  and  poverty  of  speech.  Speech abnormalities often appear in the symptoms of someone who has schizophrenia by repeating the same word or phrase over and over again.